2021
DOI: 10.1002/admt.202100225
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Transparent Metal Nanowire Microelectrode Arrays and Interconnects for Electrophysiology, Optogenetics, and Optical Mapping

Abstract: Transparent microelectrodes have recently emerged as a promising approach for crosstalk‐free multifunctional electrical and optical biointerfacing. High‐performance flexible platforms that allow seamless integration with soft tissue systems for such applications are urgently needed. Here, silver nanowires (Ag NWs)‐based transparent microelectrode arrays (MEAs) and interconnects are designed to meet this demand. The nanowire networks exhibit a high optical transparency >90.0% at 550 nm, and superior mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 59 publications
2
39
0
Order By: Relevance
“…Our group has developed and tested a range of bioelectronics that stimulate and monitor cardiac electrophysiology 12,13,[16][17][18][19] . Earlier, we tested a miniature implantable pacemaker using an external jugular approach in mice 20 .…”
Section: Development Of the Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has developed and tested a range of bioelectronics that stimulate and monitor cardiac electrophysiology 12,13,[16][17][18][19] . Earlier, we tested a miniature implantable pacemaker using an external jugular approach in mice 20 .…”
Section: Development Of the Protocolmentioning
confidence: 99%
“…Successful implantation strongly depends on operator experience. The operators involved in our studies 12,13,[16][17][18][19] were all surgical residents who all had at least 2 years of experience in general surgery. Operators experienced in small animal dissection also achieved success with this procedure even without formal medical-level general surgery training.…”
Section: Expertise Needed To Implement the Protocolmentioning
confidence: 99%
“…[8,9] Such devices have been made possible by taking advantage of novel transparent conductive materials such as atomically thin graphene, [10,11,12] indium tin oxide (ITO), [13,14] metal grid bilayers, [15,16] or nanocomposite percolation networks. [17][18][19] However, each of these materials has significant drawbacks. Transparent electrodes based on graphene face challenges in scaling up for commercial production, due to the high cost and low yield inherent in synthesizing and transferring relatively large areas of defect-free graphene to insulating substrates.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on the evaluation of the mechanical properties of Ag nanowire electrodes subjected to bending [23][24][25]. For example, Jin et al reported 2 of 8 Ag nanowire transparent electrodes for application in flexible transparent heaters; bending tests were performed to confirm the flexibility of the electrodes under 100 cycles of bending [23].…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant change in resistance during bending. Chen et al demonstrated Ag nanowire electrodes on a polyethylene terephthalate (PET) substrate, for application as a biosensor [24]. To confirm the mechanical stability, 100,000 bending cycles, under a 5 mm radius, were imposed on the electrodes, which resulted in a negligible change in resistance during bending.…”
Section: Introductionmentioning
confidence: 99%